Bone cement distribution in the vertebral body affects chances of recompression after percutaneous vertebroplasty treatment in elderly patients with osteoporotic vertebral compression fractures - Zhang L; Wang Q; Wang L; Shen J; Zhang Q; Sun C (Clinical Interventions in Aging, 2017)
Liang Zhang, Qiang Wang, Lin Wang, Jian Shen, Qiwei Zhang, Changtai Sun Department of Orthopedics, Beijing Hospital, National Center of Gerontology, People’s Republic of China Objective: Percutaneous vertebroplasty (PVP) is a surgical procedure that has been widely used to treat patients suffering from osteoporotic vertebral compression fractures (OVCFs). The procedure involves injection of bone cement into a fractured vertebra. In this study, we investigated whether the distribution of the cement in the vertebral body is related to the occurrence of recompression after surgery. Patients and methods: A total of 172 patients diagnosed with OVCF, from January 2008 to June 2013, were retrospectively reviewed. Fifty of these patients experienced recompression after surgery during the follow-up period (recompression group), and 122 patients had no recompression observed during the follow-up period (control group). Statistical analysis was performed to compare clinical and operative parameters between these two groups. Results: Differences were found in bone cement distribution between the recompression group and control group (P=0.001). Patients with bone cement distributed around both upper and lower endplates had a significantly less incidence of recompression (4/50 patients), when compared to other patterns of cement distribution (eg, below upper endplate, above lower endplate, and in the middle of vertebral body). The logistic multiple regression analysis also indicated that patients with bone cement distributed around both the upper and lower endplates had a lower risk of recompression when compared to patients with bone cement distributed in the middle of vertebral body (odds ratio =0.223, P=0.003). Conclusion: We herein suggest that the control of bone cement distribution during surgery provides beneficial effects on reducing the risks of recompression after PVP treatment in patients with OVCF. Keywords: elderly, OVCF, PVP, bone cement